Hifzh Mal: Premium Payment Due at PT Takaful Keluarga RO Al-Jannah Agency Sagulung Batam - Fadhila Sukur Indra; Febri Faila; Andi Muhammad Fuad; A Zamakhsyari Baharuddin (Syarah: Jurnal Hukum Islam dan Ekonomi, 2025)
The term premium in insurance is no longer unfamiliar to the public, including insurance customers. Premiums are paid on a regular basis (monthly, quarterly, semi-annually, or annually). However, many customers face financial or non-financial difficulties that result in late premium payments, as was the case with insurance customers at PT Takaful Keluarga RO Al-Jannah Agency Sagulung Batam. The difficulties experienced also impact individuals and companies, including insurance companies, due to the large number of participants who are late in paying their premiums. This study aims to examine the issue of late premium payments at PT Takaful Keluarga RO Al-Jannah Agency Sagulung, Batam, and how premium payment delays are viewed from the perspective of the maqasid syariah hifz mal. This study is a field study using qualitative methods, with data collection techniques through interviews and observations. Analysis was conducted using inductive reasoning. The research findings indicate that, from the perspective of the maqasid syariah hifz mal, delays in premium payments by customers do not affect the benefits customers receive from insurance products. However, if customers consistently fail to make premium payments, their insurance policies will automatically become inactive or void, and customers will lose the benefits they receive.